39 MYALGIA DOES NOT CORRELATE WITH CREATINE PHOSPHOKINASE LEVELS IN STATIN TREATED PATIENTS. (1st March 2005) - Vasu, S.; Kelly, P.; Caso, G.; Gelato, M.; McNurlan, M.; Lawson, W. E.
Abstract : Background: Myopathic pain is a feared complication of HMG CoA reductase inhibitor (statin) therapy, due to associated rhabdomyolysis. The incidence of rhabdomyolysis is low, but myalgias, fatigue and weakness are frequent in statin treated patients and often play a decisive role in patient adherence to the prescribed treatment. Preliminary evidence has implicated mitochondrial defects in ATP production as responsible for these symptoms in patients on chronic statin therapy. Methods: Prospectively studied patients on chronic statin therapy (with simvastatin or atorvastatin) with complaints of muscle pain, weakness, fatigue had their myalgias graded on a validated pain scale (range 0-10). Creatine phosphokinase (CPK) values were obtained and correlated with the patients' self-rated discomfort, statin choice and dosage. The patients participated in a randomized blinded trial of coenzyme Q10 or vitamin E supplementation with the statin choice and dosage held constant. Pain scale and CPK were repeated at the end of 1 month. Statistical testing included measurement of correlation coefficients, Fisher exact test with significance at p<0.05. Results: A total of 41 patients (16 atorvastatin 10-80 mg/day; 25 simvastatin 10-80 mg/day) were enrolled. On entry the average pain score was 4.7 (range 0-8) and the average CPK was 138.8 (range 34-573 mg/dL). There was no significant baseline correlation between pain score and CPK (lowest versus highest CPK quartile 5.4 versus 4.2 mean pain score; p = NS). There was no significant difference in baseline pain score between atorvastatin versus simvastatin (5 versus 4.5 respectively; p = NS) treated patients and no significant correlation in either group of pain severity with statin choice (correlation coefficients -0.13 atorvastatin, -0.47 simvastatin) or dose. After one month pain scores improved (-3 mean) in 20 patients and remained the same or worsened (+0.7 mean) in 21 patients. There was no relation between the magnitude or direction of change in pain score and the change in the repeat CPK. The mean CPK increased by 15.3 mg/dL in the improved pain group and decreased by 14.7 mg/dL in the group with the same or worsened pain; p = NS. Conclusions: Myalgias, fatigue and weakness not associated with marked increases in CPK are frequent in patients treated with statins. Traditional CPK testing is unreliable for confirming the presence and severity of the patient's symptoms and assessing changes in severity. Further work is necessary to develop an objective marker to detect, confirm and quantitate myalgias, fatigue, and weakness associated with statin therapy.